Demonstration Of Supplementary Food Preparation Using Tempe and Moringa Pudding - Rizki Eka Sakti Octaviani; Dhian Fitri Anggraini; Dinaryati Mawardani. T (Indonesia Berdaya, 2026)
Nutritional problems are still the main health issue in Indonesia, including in Labibia Village, Mandonga District, Kendari City. Cases of Chronic Energy Deficiency (KEK) in pregnant women and toddlers T in toddlers show the need for community-based nutrition interventions. One of the efforts made is through a demonstration of making Supplementary Feeding (PMT) made from local ingredients "Moringa Lumen Tempeh Pudding" as a form of empowerment and practical nutrition education for pregnant women, mothers under five, and posyandu cadres. This activity aims to increase participants' knowledge and skills in processing nutritious local food into healthy and attractive menus. The implementation method includes nutrition counseling and hands-on practice of making PMT by involving the community in a participatory manner. The results of the activity showed an increase in participants' understanding of the benefits of tempeh and moringa leaves as a source of protein, vitamins, and minerals to prevent KEK and Toddler T. In addition, participants were able to repractice recipes independently at home. This program has a positive impact on improving family skills in providing nutritious food and encouraging the use of local food as a food security strategy and sustainable nutrition improvement at the household level.